The Strange Case of Dr. Magelssen and Mr. Hofmann - Ole Martin Moen (Norsk Filosofisk Tidsskrift)
I argued, in the article “Is prostitution harmful?”, that if one holds that casual sex is not per se harmful, one should hold that neither is prostitution. Bjørn Hofmann and Morten Magelssen make the case that my article is methodologically flawed – so flawed, in fact, that it can serve as a cautionary tale about how this type of ethical work should not be done. Are they right?